2022
DOI: 10.1155/2022/2767735
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Mobile Wallet App Characteristics on Online Impulse Buying: A Moderated Mediation Model

Abstract: The adoption of cashless payment methods compels impulse buying. This research studies impulse purchase behavior by focusing on E-wallet app characteristics, a field where empirical research is still scarce. This paper is aimed at developing and testing a theoretical model to examine a moderated mediation model of mobile wallet app characteristics and impulse buying through perceived enjoyment moderated by mobile wallet user experience. An online survey acquired 208 valid responses from active E-wallet users. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…Table 2 depicts the mediation analysis results on four hypotheses (H24 to H27). Similar to the findings of Lee et al (2022), S and PE did not mediate the relationship between PI and IB due to the insignificant indirect effects. Conversely, PE fully mediates VA and IB.…”
Section: Mediation Effectssupporting
confidence: 81%
See 1 more Smart Citation
“…Table 2 depicts the mediation analysis results on four hypotheses (H24 to H27). Similar to the findings of Lee et al (2022), S and PE did not mediate the relationship between PI and IB due to the insignificant indirect effects. Conversely, PE fully mediates VA and IB.…”
Section: Mediation Effectssupporting
confidence: 81%
“…Moes et al (2022) found that PI indirectly promotes impulsive purchase behavior via the perspective of self-agency. Meanwhile, Lee et al (2022) discovered that PE partially mediates the relationship between VA and IB. Hasim et al (2020) found a complementary partial mediation in which PE intervenes in the relationship between monetary incentives and IB.…”
Section: Mediating Roles Of Satisfaction and Perceived Enjoymentmentioning
confidence: 99%
“…Additionally, the study conducted in H17 provides evidence that positive user experiences contribute to the decision-making process regarding payments [246]. Therefore, stimulating intrinsic motivations is critical to converting spending intention, as brand managers can create meaningful experiences and strong emotional bonds to improve loyalty and premium intention [247]. In terms of indirect factors, those influencing immersion and intention to pay are ease of use, perceived usefulness and aesthetic appeal.…”
Section: The Influencing Factors Of Immersion and Intention To Paymentioning
confidence: 99%
“…This study is motivated to explore the complex and intriguing behavioural intentions of e-wallet adoption, an area where empirical research is still lacking (Lee et al, 2022) Specifically, the TAM model in this study was used to examine the following: i. The significant effect of perceived ease of use on the perceived usefulness of e-wallet apps for making payments.…”
Section: Purpose Of the Studymentioning
confidence: 99%